AWARENESS OF FACTORS RESPONSIBLE FOR VESICOVAGINAL FISTULA AMONG HAUSA WOMEN IN NIGERIA - RN, Dr. Oluwakemi Ajike Kolade; Victoria Olufunmilayo Hanson; Makinde , Olufemi Yinyinola; Abolarinwa , Peter Babatunde (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2019)
Vesico-vaginal fistula (VVF) has been a major health challenge with consequences on the affected women’s health physically and emotionally, as well as their financial and social status. Delivery of a baby should be a period of joy, but for more than half a million women, their pregnancy and childbirth end in death while some develop vesico vaginal fistula. Vesicovaginal fistula is an abnormal communication between the bladder and the vagina leading to continuous leakage of urine through the vagina. Little is known about the perception of pregnant women about obstetric fistula and this group of women are those who are at risk of the disease. This could increase in maternal morbidity rate and impede development goals such as Sustainable Development Goals SDGs in Nigeria. Aim: investigate the awareness of factors responsible for vesico-vaginal fistula among Hausa women in Nigeria. Research design: The descriptive survey design was used in this study and Hausa women within or above the reproductive age bracket of 13-20 was used. Setting: Shasha Community in Ado Local Government area, Ekiti State, Nigeria. A simple random sampling technique. Sample: 200 respondents Tool: questionnaire was used to obtain information from respondents and was subjected to validity and reliability. Data collected were analyzed using frequency and percentage and ANOVA. Result: The study revealed that the level of awareness of Vesico vaginal fistula and its risk associative factors among Hausa women is very low. Also, the socio-economic status of Hausa women in the Hausa speaking community is very low and this has affected the level of awareness of VVF and its associative factors. In addition, several harmful practices exist in the Hausa speaking community. Conclusion: socio-economic status of Hausa women is an important factor that could increase the level of awareness of VVF and its causative factors. it is important that the government and other NGO interested in the empowerment of women should endeavor to empower Hausa women to increase their socio-economic status in the community towards enhancing the level of awareness of VVF, and its associative factors.